Diagnosis and treatment of hereditary tyrosinemia in Japan. Issue 1 (25th February 2015) - Nakamura, Kimitoshi; Matsumoto, Shirou; Mitsubuchi, Hiroshi; Endo, Fumio
Abstract: Hereditary tyrosinemia is an autosomal recessive inherited disease that manifests as three types (types I–III). We conducted a nationwide survey of this disease in Japan, and here review the results in relation to prevalence, clinical characteristics, and treatment and diagnosis. A definitive diagnosis of tyrosinemia type I is difficult to obtain based only on blood tyrosine level. Detection of succinylacetone using dried blood spots or urinary organic acid analysis, however, is useful for diagnosis. In tyrosinemia type I, dietary therapy and nitisinone (Orfandin®) are effective. Prognosis is greatly affected by the complications of liver cancer and hypophosphatemic rickets; even patients that are treated early with nitisinone may develop liver cancer. Long‐term survival can be expected in type I if nitisinone therapy is effective. Prognosis in types II and III is relatively good.